2010
DOI: 10.1038/jhh.2010.89
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and fibrinogen: age-modulated relationships with blood pressure components

Abstract: Data from a cross-sectional population-based study carried out in the town of Bollate (Milan) were used to verify whether there is an age-modulated relationship between the components of blood pressure (BP) and plasma uric acid and fibrinogen levels. Changes in uric acid and fibrinogen levels in relation to diastolic BP (DBP), systolic BP (SBP), mean arterial pressure (MAP) and pulse pressure (PP) in 820 subjects aged 42-59 years and in 509 subjects aged 60-74 years were estimated from general linear models ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“… 23 Likewise, higher BP even within normal range was verified to be associated with a higher risk of other metabolic disorders, which include diabetes, osteoporosis and hyperuricemia. 24 27 These studies may suggest that the “normal BP” may be not the real normal as we have previously considered, especially when targeted to special diseases, such as NAFLD. 22 , 23 …”
Section: Discussionmentioning
confidence: 90%
“… 23 Likewise, higher BP even within normal range was verified to be associated with a higher risk of other metabolic disorders, which include diabetes, osteoporosis and hyperuricemia. 24 27 These studies may suggest that the “normal BP” may be not the real normal as we have previously considered, especially when targeted to special diseases, such as NAFLD. 22 , 23 …”
Section: Discussionmentioning
confidence: 90%
“…More specifically, plasma uric acid levels significantly predict diastolic hypertension, but not systolic hypertension (35, 36). However, this association decreases as patients age (37) and is not found in elderly patients (36, 38-40). The weakening relationship between uric acid and hypertension with age has a few possible explanations.…”
Section: Uric Acid and Hypertensionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that high plasma uric acid levels are positively associated with increased incidences of hypertension in adults (Chu et al 2000). More specifically, plasma uric acid levels significantly predict diastolic hypertension, but not systolic hypertension (Leite 2011). A relationship between elevated UA concentration in plasma and the occurrence of hypertension has been very well documented in many clinical and epidemiological studies (Messerli et al 1980, Nagahama et al 2004, Alper et al 2005, Sundstrom et al 2005.…”
Section: Introductionmentioning
confidence: 97%